Miguel de Unamuno’s Philosophy of Religion as a Bultmannian Demythologization: The Problem of Transcendence - Fediajevas, Algirdas (Religija ir kultūra, 2015)
[full article and abstract in Lithuanian; abstract in English] This article deals with Miguel de Unamuno’s religious thinking through the prism of Rudolf Bultmann’s demythologization. These authors, which are bound by a common philosophical and cultural context, ground and develop their ideas on the plane of a concrete human, who resides in a secularized world; Unamuno names such a subject as “the man of flesh and bones.” While understanding that the traditionalist, mythological and metaphysical elements of Christianity cannot satisfy a person living in a secularized world, Unamuno and Bultmann demythologize the Christian Message and underline in it that which is told, in the form of an appeal, about the human existence and that which applies to the main questions arising from its concern about itself. Unamuno considers that the core of the Christian Message is the promise of the immortality of every “man of flesh and bones,” which is possible because of Christ’s resurrection; Bultmann, on the other hand, believes this core to be in the call for a free and authentic existence. The main separation between the authors’ views is how they treat the relation between the concrete human and transcendence: for Unamuno, the relation with transcendence is an immanent need for “the man of flesh and bones,” the only possible way for its immanence (understood both in the existential and metaphysical senses) to be fulfilled; for Bultmann, the relation between the concrete human and transcendence is an eschatological event and the break of immanence both in the relation between the concrete human and the world as well as between the concrete human and itself.